Salpingoovarectomy Using Senhance® Robotic System: a Case Report - Šiaulys, Raimondas (Lietuvos chirurgija, 2019)
[full article and abstract in Lithuanian; abstract in English] A case of salpingoovarectomy using Senhance® robotic system – surgery technic, benefits and results are described in this article.